Technology Entrepreneurship Project (ENT 600) : Umeko Company / Muhammad Zulhemi Othman Ariff - Othman Ariff, Muhammad Zulhemi; Mohd Sani, Muhamad Syazwan Ajmal; Saini, Faridatul Wahida; Mohd Sani, Anis Safiah; Abd Majid, Muhammad Daniel (2021)
Staying ahead and following the changes happening in the industry is one of the crucial parts in business. So basically, Umeko is a company that will produce furniture which is multipurpose chair. The idea of this product is to give full satisfaction which is the comfortability and this product actually have been focusing to the people that use chair for a longer period of time. The speciality of this product actually came from the ergonomic concept that we have been emphasize and a few unique function that will help consumer and will increase the productivity of work when using this multipurpose chair. Besides, the concepts that we want to propose here is the backpain can be reduce when people are using this multipurpose chair because the features that have been use in this multipurpose are really helpful which is it comes with automatic adjustment for back rest, leg rest and arm rest that will give maximum comfortability to the user. Essentially, our main target market are people that working in office. This is because they are using chair for a longer period of time. Some research have been done among the workers, most of them complained that they got back pain and neck pain after sitting to long in order to complete their tasks. Other than that, our target market is students and teachers. In this pandemic situations, the student and teachers will undergo online learning. So they will use their laptop for a longer period of time. Many of them also complained that they are not comfortable while learning. We targeted that we will sell 100 unit of this multipurpose chair per month. Moreover, the competitive advantages that we have in this product is cable plug, automatic adjustment for back rest, leg rest and arm rest, durable wheels and foldable extension tray. We designed this product with that unique features because it will be helpful to users and other competitors does not have this cool features. In addition, our company estimates our profits will gradually grow from 5% in second year to 10% in the third years and this shown that our company undergoes cash-flow positive started from the second year. So basically, our company will be separated into 4 departments, which is administration department, operational department, financial department and marketing department. The management of our company will be lead by the general manager which is Muhammad Zulhelmi Bin Othman Ariff. He will supervise the routine business operations, educating low-level supervisors and workers, establishing and implementing strategies for development and making decision and signing agreement. Next, for the administration department will be lead by an administration manager which is Muhammad Daniel Firdaus Bin Abd Majid. He will maintain administrative personnel by employee recruitment, selection, orientation and training.